Book as a Representation Medium of the Author’s Ideology - Nova Darmanto; Nurul Akmalia (2021)
The texts written by the authors have had a tremendous influence on human civilization. The book was used as a control tool for royal power institutions by creating rules through language discourse. This study intends to analyze the media of books to represent the authors’ ideologies. The method used in this research is descriptive qualitative by conducting analyses through literature studies and representation approach. This study indicates that writing a book represents and forms its identity. The authors make writing in the form of messages on book by using language to explore knowledge and find information that is different from the ideological ideas. Each writer’s ideology emphasizes his efforts to create a thought system through symbolic practices structured by messages in written text. It will then affect the provision of knowledge or information to readers. Not only that, but publishers also took part in determining messages in the book. Publishers have many interests. The interests are various, including political, economic, and religious interests. The contention between book publishers’ policies and theideology of writers ended with the emergence of the decision to publish a written text as a symbol that reflects the author’s ideology.